Quantum Optics - Agarwal, G. S. 1946- (Cambridge: Cambridge University Press, 2013)
"In the last decade many important advances have taken place in the field of quantum optics, with numerous potential applications. Ideal for graduate courses on quantum optics, this textbook provides an up-to-date account of the basic principles of the subject. Focusing on applications of quantum optics, the textbook covers recent developments such as engineering of quantum states, quantum optics on a chip, nano-mechanical mirrors, quantum entanglement, quantum metrology, spin squeezing, control of decoherence and many other key topics. Readers are guided through the principles of quantum optics and their uses in a wide variety of areas including quantum information science and quantum mechanics. The textbook features end-of-chapter exercises with solutions available for instructors at www.cambridge.org/9781107006409. It is invaluable to both graduate students and researchers in physics and photonics, quantum information science and quantum communications"--
Machine generated contents note: 1. Quantized electromagnetic field and coherent state representations; 2. Nonclassicality of radiation fields; 3. Two mode squeezed states and quantum entanglement; 4. Non-Gaussian nonclassical states; 5. Optical interferometry with single photons and nonclassical light; 6. Polarization and orbital angular momentum of quantum fields; 7. Absorption, emission, and scattering of radiation; 8. Partial coherence in multimode quantum fields; 9. Open quantum systems; 10. Amplification and attenuation of quantum fields; 11. Quantum coherence, interference and squeezing in two-level systems; 12. Cavity quantum electrodynamics; 13. Absorption, emission and scattering from two-level atoms; 14. Quantum interference and entanglement in radiating systems; 15. Near-field radiative effects; 16. Decoherence and disentanglement in two-level systems; 17. Coherent control of the optical properties; 18. Dispersion management and ultraslow light; 19. Single photons and nonclassical light in integrated structures; 20. Quantum optical effects in nano-mechanical systems; Index.
Includes bibliographical references and index.
Keywords: Quantum optics -- Textbooks; SCIENCE / Optics; Physics